Evaluación de los resultados de cementación de la sección intermedia de un pozo inyector de un campo en la cuenca Llanos Orientales por medio de la simulación del uso de la tecnología cabeza rotativa de cementación (2016)
This paper exposes technical and economic aspects that must be taken into account far the realization of a dynamic cementation, compared with the technical and economic aspects that took place in one of the wells that had unsatisfactory cementation results. Subsequently, through a simulation of the cementing operation with rotation parameter at different frequencies, proceeds to compare the obtained results with the results taken from the well login that has been studied. Finally, the project will be financially analyzed thought the income comparison between the advantages and disadvantages for ECOPETROL S.A to execute the dynamic cementation against the conventional cementation that was implemented in the studied well.